2016
DOI: 10.9740/mhc.2016.07.171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of electrocardiogram monitoring in patients on psychotropic medications that have a risk of QT prolongation

Abstract: Introduction:Many psychotropic medications carry a risk of prolonging the QT interval and increasing the risk of developing Torsade de pointes (TdP). The goal of this study was to evaluate whether patients taking psychotropic agents with a known risk of TdP are being monitored at a community hospital through the use of electrocardiograms (EKGs).Methods:This was a retrospective chart review of 100 adult patients—50 from general medicine floors and 50 from psychiatric units—who were taking at least one psychotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Common findings in the literature review which guided the development of this algorithm include the use of CredibleMeds ® as an important evidence-based resource, as well as the importance of cardiac risk stratification in the assessment and management of drug-induced QTc prolongation. Studies have shown that prescribers do not routinely screen for cardiac risk factors in psychiatric patients 53,56,57…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common findings in the literature review which guided the development of this algorithm include the use of CredibleMeds ® as an important evidence-based resource, as well as the importance of cardiac risk stratification in the assessment and management of drug-induced QTc prolongation. Studies have shown that prescribers do not routinely screen for cardiac risk factors in psychiatric patients 53,56,57…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because ECG monitoring may not be possible or readily accessible in both outpatient and inpatient settings, or in all psychiatric facilities, the algorithm developed highlights the importance of assessing the associated risk factors as early as possible before making recommendations on the use of medications with QTc-prolonging risk, primarily those listed as Category 1–3 by CredibleMeds ® or those that are known inhibitors of the hERG IKr channel 11,49,53,56–58. Current research initiatives, such as the Comprehensive in vitro Proarrhythmia Assay (CiPA), are developing and validating a model to test the proarrhythmic risk of drugs by assessing the effect of drugs on multiple ion channels and integrating ECG analysis in early phase I clinical trials to better predict proarrhythmic risk 59.…”
Section: Discussionmentioning
confidence: 99%